Organisasi Islam dan peranannya dalam pengembangan pendidikan Islam di Australia - Fery, Andi; Sayuti, Ujang; Al Ikhlas,; Zulmuqim,; Zalnur, Muhammad (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2023)
Australia, although geographically close to Asia, maintains a cultural affinity with the Western world. The majority of the population adheres to Christianity, but Islam has grown rapidly in the country. The growth of Islam in Australia is inseparable from the active role played by the Muslim community, which consists of individuals who migrated to Australia for various reasons such as economic and political motives. To integrate and preserve their Islamic identity, Muslims in these communities make various efforts. Based on this background, this study formulates several problem formulations as follows: first, the history of the entry of Islam into Australia; second, the development of Islam and Muslim communities in Australia; and third, the role of Australian Muslim communities in the development of Islamic education in Australia. In conducting this research, the author uses a Library Research approach, specifically using historical research methods which include heuristics, interpretation, verification, and historiography to present a writing that is easy to understand. Abstrak Negara Australia, meskipun secara geografis dekat dengan Asia, tetapi mereka tetap mempertahankan kedekatan budaya dengan dunia Barat. Mayoritas penduduknya memeluk agama Kristen, namun Islam telah berkembang pesat di negara ini. Pertumbuhan Islam di Australia tidak terlepas dari peran aktif yang dimainkan oleh komunitas Muslim, yang terdiri dari individu-individu yang bermigrasi ke Australia karena berbagai alasan seperti motif ekonomi dan politik. Untuk mengintegrasikan dan melestarikan identitas keislaman mereka, umat Islam dalam komunitas-komunitas ini melakukan berbagai upaya. Berdasarkan latar belakang tersebut, penelitian ini merumuskan beberapa rumusan masalah sebagai berikut: pertama, sejarah masuknya Islam ke Australia; kedua, perkembangan Islam dan komunitas Muslim di Australia; dan ketiga, peran komunitas Muslim Australia dalam pengembangan pendidikan Islam di Australia. Dalam melakukan penelitian ini, penulis menggunakan pendekatan library research, khususnya menggunakan metode penelitian sejarah yang meliputi heuristik, interpretasi, verifikasi, dan historiografi untuk menyajikan tulisan yang mudah dipahami.